2015
DOI: 10.1155/2015/890957
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Symptoms of Human Rotavirus Infection Observed in Children in Sokoto, Nigeria

Abstract: Rotavirus has been identified among the most important causes of infantile diarrhoea, especially in developing countries. The present study was undertaken to determine the occurrence and clinical symptoms of human rotavirus disease among children presenting with varying degree of diarrhoea in selected urban hospitals in Sokoto metropolis, Nigeria. Diarrhoea samples were collected from 200 diarrheic children younger than 5 years of age and tested using a commercially available DAKO Rotavirus ELISA kit which det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 24 publications
1
17
3
Order By: Relevance
“…Respiratory symptoms were observed in 60% of our patients. Alkali et al 17 and Surajuddin et al 13 in Nigeria found respiratory symptoms in only 3-9% and 8% patients respectively which may be due to difference in strains in different geographical areas. Perianal excoriation due to secondary transient lactose intolerance was seen significantly more in rotavirus positive diarrhoea in the present study and is also described classically 5 .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Respiratory symptoms were observed in 60% of our patients. Alkali et al 17 and Surajuddin et al 13 in Nigeria found respiratory symptoms in only 3-9% and 8% patients respectively which may be due to difference in strains in different geographical areas. Perianal excoriation due to secondary transient lactose intolerance was seen significantly more in rotavirus positive diarrhoea in the present study and is also described classically 5 .…”
Section: Discussionmentioning
confidence: 93%
“…As per 2008 estimates of global rotavirus linked mortality, 23% of all rotavirus deaths were in the Indian subcontinent 17 and the main cause reported was severe dehydration. Rotavirus immunization programme planned by the Government of India may substantially reduce morbidity, cost of treatment and loss of working days for parents 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, respiratory signs are often found during RV gastroenteritis. Patients shed virus via stools acts as a major reservoir for infecting others …”
Section: Clinical Featuresmentioning
confidence: 99%
“…The study has shown that fever is presented in RV infection as manas 45-84%. Alkali et al (2015) reported fever was found among 51% cases. Vomiting is caused by disturbance of motoric activity of the stomach such as delayed emptying of fluid content that can cause mild to severe dehydration which is life-threatening children.…”
Section: Discussionmentioning
confidence: 91%
“…Vomiting is caused by disturbance of motoric activity of the stomach such as delayed emptying of fluid content that can cause mild to severe dehydration which is life-threatening children. (Nguyen et al, 2004;Alkali et al, 2015) The analysis of clinical manifestations is based on several categories, including duration, frequency, diarrhea level and presence of blood and consistency. The results showed no differences between clinical manifestations in the RV and non-RV groups (p > 0.05) (Djojosugito et al, 2017).…”
Section: Discussionmentioning
confidence: 99%